2021
DOI: 10.1016/j.yebeh.2021.108160
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccination in patients with epilepsy: First experiences in a German tertiary epilepsy center

Abstract: Introduction Due to the high demand for information regarding COVID-19 vaccination in people with epilepsy (PWE), we assessed the symptoms and seizure control of PWE following their COVID-19 vaccination. Methods All adult patients who were treated at our center were asked to report on their vaccination status and, if vaccinated, about their experiences following their first COVID-19 vaccination with regard to adverse effects and seizure control. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
112
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(130 citation statements)
references
References 17 publications
11
112
1
2
Order By: Relevance
“…In their study, only 6.1% of the vaccinated group had seizure worsening; they reported a patient who had seizure worsening experience (status epilepticus) within the last 3 months before the vaccination who had a fever for 3 days post-vaccination ( 28 ). Another study of 54 PWE in a German tertiary epilepsy center found that vaccination against COVID-19 appeared to be well-tolerated, supporting the recommendation of vaccination to PWE ( 29 ). However, more extensive and long-term studies are needed to evaluate the long-term safety of the different vaccines.…”
Section: Discussionmentioning
confidence: 75%
“…In their study, only 6.1% of the vaccinated group had seizure worsening; they reported a patient who had seizure worsening experience (status epilepticus) within the last 3 months before the vaccination who had a fever for 3 days post-vaccination ( 28 ). Another study of 54 PWE in a German tertiary epilepsy center found that vaccination against COVID-19 appeared to be well-tolerated, supporting the recommendation of vaccination to PWE ( 29 ). However, more extensive and long-term studies are needed to evaluate the long-term safety of the different vaccines.…”
Section: Discussionmentioning
confidence: 75%
“…The mean age of our patients was 32.47 years ( SD = 12.76). It is lower than that of European peers, which was 47.9 ( SD = 20.1) in a tertiary center in Germany and 48.2 ( SD = 19.8) in a tertiary center in Spain [ 14 , 15 ]. The demographic structure of the Turkish population can explain this difference.…”
Section: Discussionmentioning
confidence: 90%
“…The majority of the patients in our study sample had generalized epilepsy. The distribution of epilepsy types may vary among centers [ 3 , 14 , 15 ]. The drug-resistant epilepsy rate was 19.1% in our patients, similar to the literature rates [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…53 그러나 실제 COVID-19 백신 접종을 한 환자를 대상으로 한 연구에서 1차 접종을 한 54명 뇌전증 환자(18세 이상) 중 1명만 이 발작이 악화되었고, 30% 정도에서 두통, 피로, 발열 등 일반 적 인 백 신 부작 용 만 이 있었 다. 54 다 른 설 문 연구 에 서 는 COVID-19 백신을 맞은 82명의 뇌전증 환자(16세 이상) 중 5명 (6.1%)만이 발작 빈도가 증가했다고 응답하였다. 55…”
Section: 뇌전증 환자에서의 Covid-19 백신unclassified